Competency-Based Management for Organizational Development at Universidad Nacional Mayor de San Marcos - Castillo Arias, Lucía Fernanda Palmira (2021)
This study aims to contribute to the improvement of human resources management through a competency-based management model for administrative positions in the central administration that will lead to organizational development at Universidad Nacional Mayor de San Marcos. This is because, on some occasions, people who hold administrative positions lack the training required to manage, and only have technical knowledge, which is not enough to achieve the objectives determined in university’s strategic plan. Different bibliographic sources, studies related to the topic, as well as the methodology established by SERVIR were reviewed. The study revealed that no specific measures have been established for the profiles of management positions at the university, so that it is therefore necessary for the human resources office to implement a competency-based management model and enforce the established guidelines. The introduction of a new proposal based on the competencies to the university invites us to redesign the work profiles in terms of performance functions.